The future energy internet for utility energy service and demand-side management in smart grid: Current practices, challenges and future directions - Parvin K.; Hannan M.A.; Hui Mun L.; Hossain Lipu M.S.; Abdolrasol M.G.M.; Jern Ker P.; Muttaqi K.M.; Dong Z.Y. (Elsevier Ltd, 2023)
5G mobile communication systems; Cybersecurity; Demand side management; Electric power transmission networks; Electric utilities; Information management; Network security; Sustainable development; Current practices; Energy demands; Energy internet; Energy services; Future energies; Grid current; Internet based; Smart grid; Smart metering; Utility energy service; Smart power grids; demand-side management; efficiency measurement; electricity industry; energy planning; energy resource; future prospect; smart grid; sustainability; utility sector; vulnerability